Activity of preserved anaerobic sludge. Issue 2 (28th January 2020) - Doloman, Anna; Sims, Ronald C.; Miller, Charles D.
Abstract: There is a need for a broad study addressing different preservation conditions of anaerobic sludge and its activity after a prolonged storage. This study compared four different preservation methods of mesophilic anaerobic sludge for a period of up to 12 months: storage at 23 ± 2 °C, +4 °C, ‒20 °C, and freeze-dried. Anaerobic sludge was sampled from upper and bottom ports of an up flow anaerobic sludge blanket (UASB) reactor fed with microalgae and sodium acetate at organic loading rate of 5.4 gCOD/L·d. Specific methanogenic activity (SMA) tests were performed on the sludge samples after 2.5, 6, and 12 months of storage. Results demonstrated a statistically significant decrease in the SMA of the bottom port preserved sludge, but not of the upper port sludge, regardless of the method used for preservation. A varying susceptibility to the storage of the two types of the anaerobic sludge can be explained by the content of the methanogenic microorganisms, with bottom port sludge having a higher amount of the methane producing species. Interestingly, lyophilized samples were able to produce similar amounts of biogas when compared to the other three storage conditions, with the only difference of having a longer re-activation period.